2019
DOI: 10.1007/s10661-019-7327-1
|View full text |Cite
|
Sign up to set email alerts
|

Flood hazard mapping using geospatial techniques and satellite images—a case study of coastal district of Tamil Nadu

Abstract: In recent years, extreme rainfall events have resulted in several devastating floods especially in the east coast of Tamil Nadu, India. The main aim of this study is to identify the flood hazard zones in Cuddalore district by integrating spatial distribution of extreme rainfall events, slope, drainage density, soil, and geomorphology. Moderate Resolution Imaging Spectroradiometer satellite data was used to delineate the flood inundation area for the flood event which occurred in 2010 to validate the derived fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 24 publications
0
6
0
4
Order By: Relevance
“…Most of these studies have focused on the physical flood modelling of a selected portion, considering only a few controlling factors. In this study, we attempted to comprehensively assess the flood risk for the entire stretch of the coastal plain of Tamil Nadu [48,[50][51][52][53][54][55][56][57][58]. Unlike other previous attempts, this study considered all the major dimensions of flood risks on a relative scale and presented the results at micro-administrative units.…”
Section: Discussionmentioning
confidence: 99%
“…Most of these studies have focused on the physical flood modelling of a selected portion, considering only a few controlling factors. In this study, we attempted to comprehensively assess the flood risk for the entire stretch of the coastal plain of Tamil Nadu [48,[50][51][52][53][54][55][56][57][58]. Unlike other previous attempts, this study considered all the major dimensions of flood risks on a relative scale and presented the results at micro-administrative units.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to high population density, a high proportion of primary workers, female and socially weaker population make this region most vulnerable. Furthermore, this region is highly prone to cyclones, storm surges and floods (Mazumdar and Paul, 2016;Thirumurugan and Krishnaveni, 2019). Many physical vulnerability analyses have documented this stretch to be a highly vulnerable zone (Nitheshnirmal et al 2018;Balasundareshwaran et al 2019;Priya Rajan et al 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that all the highly populated coastal cities of TN viz. Chennai (Kumar and Kunte, 2012;Joerin et al 2012), Puducherry (Murali et al 2013), Cuddalore (Saxena et al 2013;Thirumurugan and Krishnaveni, 2019;Parthasarathy et al 2020), Nagapattinam (Muthusankar et al 2013), Thoothukudi (Parthasarathy and Natesan, 2015) and Kanyakumari (Kaliraj et al 2015) are vulnerable, and have experienced one or more major coastal hazards in the recent years. Implementation of effective mitigation measures and preparedness for future disasters is possible only through proper understanding of human habitations and their socioeconomic conditions (Cutter et al 2000;Mahendra et al 2011;Appelquist and Balstrøm, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…An inundation hazard map indicates the area at inundation risk and defines the areas in danger where the inundation events are probable to occur. Inundation hazard mapping is so important for urban risk management and land use planning (Thirumurugan & Krishnaveni, 2019).…”
Section: Inundation Hazard Mappingmentioning
confidence: 99%